Association between dietary acid load and risk of metabolic dysfunction-associated steatotic liver disease in patients with type 2 diabetes - Bakhshi, Hesam; Naghshi, Niayesh; Fotros, Danial; Pasand, Mohammadjavad; Hekmatdoost, Azita; Salavatizadeh, Marieh; Soltanieh, Samira; Poustchi, Hossein; Khamseh, Mohammad Ebrahim; Yari, Zahra (Frontiers in Nutrition, 2025)
ObjectiveConsidering the high prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD) among patients with type 2 diabetes and its associated complications, this study aimed to investigate the relationship between dietary acid load (DAL) and the risk of MASLD in patients with diabetes.MethodsThis cross sectional study was conducted on 200 patients aged 18 to 70 with type 2 diabetes. Of whom, 133 participants were diagnosed with MASLD based on transit elastography (Fibroscan). For biochemical evaluation of liver enzymes, lipid profile, and fasting blood sugar, venous blood samples were collected after 10–12 h of fasting. Dietary acid load was determined using a 147-item food frequency questionnaire based on PRAL (potential renal acid load) and NEAP (net endogenous acid production).ResultsA total of 108 women and 92 men with an average age of 52.2 years and an average body mass index of 28.8 kg/m2 participated in the study. After adjusting for confounders, the risk of MASLD in the third tertile of PRAL was 3.1 times higher than the first tertile (OR = 3.1, 95% CI = 1.2–7.7). After adjusting for all confounding factors, participants in the highest tertile of NEAP had nearly seven times the chance of developing MASLD compared to those in the lowest tertile, which was statistically significant (OR = 7.3, 95% CI = 2.6–20.3). Overall, the data analysis revealed a significant direct relationship between both PRAL (P trend = 0.016) and NEAP (P trend < 0.001) with the risk of MASLD.ConclusionOur analysis revealed that a higher dietary acid load is associated with an increased risk of MASLD and liver steatosis in patients with type 2 diabetes.